The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.18553/jmcp.2014.20.8.844
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Use of Comedications Reduces Adherence to Antiretroviral Therapy Among HIV-Infected Patients

Abstract: BACKGROUND: The use of highly active antiretroviral therapy has significantly reduced morbidity and mortality, thus increasing life expectancy of human immunodeficiency virus (HIV)-infected individuals, transforming HIV into a chronic disease. Accordingly, there has been an increase in the number of comorbidities concomitantly present in these individuals and also an increased use of comedications, which may negatively impact antiretroviral therapy adherence. These factors can affect adherence to antiretrovira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 39 publications
(44 reference statements)
2
41
0
1
Order By: Relevance
“…Even if the data were not statistically significant, they agree with those reported by Cantudo-Cuenca et al ,13 who noted that polymedication is a predictor of non-adherence to ARV treatment. It is important to remember that adherence is a determining factor in the effectiveness of suppressing viral replication, avoiding resistance and minimising co-morbidities 25…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Even if the data were not statistically significant, they agree with those reported by Cantudo-Cuenca et al ,13 who noted that polymedication is a predictor of non-adherence to ARV treatment. It is important to remember that adherence is a determining factor in the effectiveness of suppressing viral replication, avoiding resistance and minimising co-morbidities 25…”
Section: Discussionsupporting
confidence: 90%
“…According to the definition of the WHO, polypharmacy is ‘the administration of multiple drugs simultaneously’,12 which leads to an increase in likely drug interactions, duplication of treatment and increased adverse effects; polypharmacy is another barrier to therapeutic compliance, as it is associated with increased risk of non-adherence 13. It is estimated that the clinically relevant interactions between ARVs and concomitant medications can reach rates of 20% to 40% and could have fatal consequences 14–15.…”
Section: Introductionmentioning
confidence: 99%
“…TWLWH reported lower adherence to medications than non-transgender men, and the difference in adherence between TWLWH and non-transgender women approached statistical significance, supporting past findings (Mizuno et al, 2015; Sevelius et al, 2014; Sevelius et al, 2010). As expected, lower adherence among the TWLWH in this sample was associated with detectable viral loads and failure to achieve viral suppression, further supporting literature that adherence to medications is positively related to virologic outcomes (Cantudo-Cuenca et al, 2014; Mizuno et al, 2015). …”
Section: Discussionsupporting
confidence: 86%
“…Cantudo-Cuenca et al 20 reported that the use of multiple medications increases the risk of non-adherence and therefore it may increase the risk of hospital admission. Polypharmacy seems to be the next therapeutic challenge in HIV patients 21–23…”
Section: Discussionmentioning
confidence: 99%